The Role of Parents in the Education of Children - Himani (Universal Research Reports, 2019)
"Home education" refers to the impact of a family's educational influence on a kid. According to study, children are exposed to a broad range of influences, as well as expectations, from the people with whom they live. As part of our research, we'll look at how parents influence their children's educational experiences in the home. Families' differing educational capacities will be investigated. An enormous and difficult responsibility falls on the shoulders of the family to ensure that their children's physical and mental wellbeing as well as their general educational progress as well as their intellectual growth and development, as well as the development of better moral values, convictions, attitudes, and habits within the family as well as the broader community in which they live. Family as an institution has an obligation to nurture children's personalities so that they grow up with positive attitudes about work that serve as a basis for a more practical approach.